1993
DOI: 10.1104/pp.102.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Catabolites of Chlorophyll-Porphyrin in Senescent Rape Cotyledons

Abstract: Developing shoots of rape seedlings (Brassica napus 1.) were excised and fed with 4-['4C]5-aminolevulinic acid to label the pyrroles in chlorophyll (Chl) synthesized during the final phase of expansion and greening of the cotyledons. About 80% of 14C taken up into the cotyledons was incorporated into Chl. The subsequent incubation of labeled shoots in permanent darkness caused the rapid loss of labeled Chl while increasing proportions of 14C appeared in the fradion of water-soluble compounds. Reversedphase hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 9 publications
1
83
0
Order By: Relevance
“…2; Table 11). Three fluorescent products could be identified as FCCs by their typical absorption maxima at 320 and 360 nm (Ginsburg and Matile, 1993;Mühlecker et al, 1997; data not shown). According to its retention time on HPLC, peak 2 was found to be identical to Bn-FCC-2, whereas the minor peak 3 corresponded to Ca-FCC-2, the first identifiable product of Pheide a cleavage in the presence of enzyme preparations from ripening fruits of C. annuum (Moser and Matile, 1997).…”
Section: Fd-dependent Formation Of Primary Fccs From a Red Bilinmentioning
confidence: 99%
See 2 more Smart Citations
“…2; Table 11). Three fluorescent products could be identified as FCCs by their typical absorption maxima at 320 and 360 nm (Ginsburg and Matile, 1993;Mühlecker et al, 1997; data not shown). According to its retention time on HPLC, peak 2 was found to be identical to Bn-FCC-2, whereas the minor peak 3 corresponded to Ca-FCC-2, the first identifiable product of Pheide a cleavage in the presence of enzyme preparations from ripening fruits of C. annuum (Moser and Matile, 1997).…”
Section: Fd-dependent Formation Of Primary Fccs From a Red Bilinmentioning
confidence: 99%
“…The red bilin depicted in Figure 1 was tentatively assumed to represent an intermediary catabolite of the Pheide a to FCC conversion . According to the nomenclature of Chl catabolites proposed by Ginsburg and Matile (1993), it was named RCC.…”
Section: Fd-dependent Formation Of Primary Fccs From a Red Bilinmentioning
confidence: 99%
See 1 more Smart Citation
“…Tbese compounds bave been designated nonfluorescent chlorophyll catabolites (NCCs). Tbis new terminology for chlorophyll catabolites is proposed in Ginsburg & Matile (1993). In senescent barley leaves tbe predominant NCC, RP 14, accumulates with time.…”
Section: Pigmentsmentioning
confidence: 99%
“…It turned out., however, that in their native form and if kept in a neutral solvent, these compounds are colourless and fluorescent . A nomenclature has recently been proposed (Ginsburg & Matile, 1993), according to which the fluorescent chlorophyll catabolites are designated as FCCs. The occurrence of FCCs concomitant with chlorophyll breakdown has been observed not only in Festuca (Duggelin et al 1988(7) but also in barley (Duggelin et aL, 19886) and rape (Ginsburg & Matile, 1993), By means of radiolabelling, two of the FCCs were confirmed as catabolites of chlorophyll (Matile, Schellenberg & Peisker, 1992;Ginsburg & Matile, 1993).…”
Section: Introductionmentioning
confidence: 99%